2019
DOI: 10.3389/fneur.2018.01165
|View full text |Cite
|
Sign up to set email alerts
|

Effort and Fatigue-Related Functional Connectivity in Mild Traumatic Brain Injury

Abstract: Mental fatigue in healthy individuals is typically observed under conditions of high cognitive demand, particularly when effort is required to perform a task for a long period of time—thus the concepts of fatigue and effort are closely related. In brain injured individuals, mental fatigue can be a persistent and debilitating symptom. Presence of fatigue after brain injury is prognostic for return to work/school and engagement in activities of daily life. As such, it should be a high priority for treatment in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…Interestingly, the symptom of post concussive syndrome that is most strongly related to resilience is fatigue ( Losoi et al, 2015b ). While this symptom, in particular, has only been investigated in a few studies involving military service members (c.f., Ramage et al, 2019 ; Lewis et al, 2021 ), one study validates that persistent fatigue in this population is associated with poorer rates of return to productivity ( Mortera et al, 2018 ). Thus, relationships among mild TBI, fatigue, and potential for recovery are intertwined and particularly prevalent in military service members.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly, the symptom of post concussive syndrome that is most strongly related to resilience is fatigue ( Losoi et al, 2015b ). While this symptom, in particular, has only been investigated in a few studies involving military service members (c.f., Ramage et al, 2019 ; Lewis et al, 2021 ), one study validates that persistent fatigue in this population is associated with poorer rates of return to productivity ( Mortera et al, 2018 ). Thus, relationships among mild TBI, fatigue, and potential for recovery are intertwined and particularly prevalent in military service members.…”
Section: Introductionmentioning
confidence: 86%
“…Additionally, Ramage et al (2019) found that the strength of the left claustrum's connections with the rostral and dorsal anterior cingulate cortex, medial frontal gyrus, and right inferior frontal gyrus (orbital and opercular) was correlated with fatigue evidenced by mTBI participants. While some of these additional functionally connected regions are considered part of the CO network, the others are more consistently considered to be within the FP network.…”
Section: Introductionmentioning
confidence: 97%
“…Left insula and superior medial frontal gyrus correlated with fatigue. The authors propose a complex link between effort and fatigue and that it may be related to an inefficient neuronal system [73]. Activation assessed with rCBF within the cerebellar cortex correlated with PASAT, measuring information processing and sustained and divided attention in controls, while mTBI participants with self-reported cognitive fatigue showed significant correlations in the inferior frontal and superior temporal cortices [74].…”
Section: Brain Imaging In Relation To Tbi and Fatiguementioning
confidence: 98%
“…CE : Left anterior insula, rostral anterior cingulate cortex, and right‐sided inferior frontal regions (Ramage et al, 2019)…”
Section: Discussionunclassified